Sosialisasi Terhadap Undang-Undang Nomor 24 Tahun 2011 Tentang Peran Hukum Kesehatan Dalam Melindungi Peserta Program Badan Penyelenggara Jaminan Sosial Kesehatan - F, Fitriani; Siahaan, Ade Yuliany; Batubara, Sonya Airini (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Law Number 24 of 2011 has a very important role in health law in ensuring the protection of participants in the National Health Insurance program (BPJS Kesehatan). The purpose of this research is to find out the protection of the Rights of BPJS Participants Based on Law No. 24 of 2011 and the Law Enforcement Mechanism in Protecting the Rights of BPJS Participants. This research uses a normative juridical approach. The data used in the study is secondary data. Secondary data is obtained by studying documents by reading, studying and analyzing literature in the form of laws and regulations, books and other sources related to this research. In the study, this law provides a legal basis for the implementation of the national health insurance program, which aims to promote public welfare by providing equal access to quality health services. The health law serves to protect the rights of BPJS participants by ensuring that they receive health services that meet the set standards without discrimination. Furthermore, this law mandates the state to provide comprehensive and inclusive health insurance. Through the role of BPJS Kesehatan, health laws also regulate the supervision and enforcement of accountability from health service providers, both in terms of service quality and financial management.